Intentional Replantation of Permanent Mandibular First Molar to Remove Overextended Gutta Percha: A Case Report - Sanchit Kumar; Avninder Kaur; Reetu Singh; Neha Kashav; Tshering Yangkila Bhutia (Dental Journal of Advance Studies)
Intentional replantation has been traditionally accepted as last resort in treatment of teeth where surgical endodontic treatment is contraindicated. Iatrogenic breakage of Gutta percha beyond apex does predispose such treatment needs, especially, where vital structures surround the operational area. This case report describes a case of adolescent male individual where iatrogenic endodontic complication was successfully managed and presents one-year follow-up of uneventful healing.